Notary's Liability for Falsified Power of Attorney to Sell (Study of Court Decision Number 773/Pid.B/2021/PN Smg) - Hapsari, Aulia Rizky; Arifulloh, Achmad; Djunaedi, Djunaedi (TABELLIUS: Journal of Law, 2026)
Forgery of power of attorney deeds is a common problem in notarial practice in Indonesia. As authentic evidence, power of attorney deeds should provide legal certainty and protection, but in practice, notaries often make irregularities in their preparation, resulting in discrepancies between the contents of the deed and the legal facts, resulting in disputes and legal uncertainty. This study aims to analyze the notary's responsibility for forged power of attorney deeds and the judge's considerations in Semarang District Court Decision Number 773/Pid.B/2021/PN Smg. The approach used in this study is a normative juridical approach with a type of normative legal research that focuses on the study of laws and court decisions related to the research problem. The data used are secondary data obtained through literature studies, including primary, secondary, and tertiary legal materials. Data analysis was conducted using a qualitative descriptive method by systematically and logically describing and interpreting the data to answer the research problem. The results of the study show that notaries can be held accountable for administrative, civil and criminal matters if they are proven to have been intentional or negligent in carrying out their authority, resulting in the forgery of a power of attorney to sell. The judge considered that the creation of a deed without the presence and signature of the principal fulfilled the elements of forgery of a deed as regulated in Article 264 paragraph (1) of the Criminal Code, which confirms that notaries are not immune to criminal sanctions.